MANAGEMENT OF SCHOOL AND COMMUNITY RELATIONS IN BUILDING A POSITIVE IMAGE OF SCHOOLS (CASE STUDY OF SDN 1 RATOLINDO) - Suci Indasari; Novianty Djafri; Arwildayannto (International Journal of Teaching and Learning, 2025)
This research aims to describe; (1) the role of school and community relations; (2) school and community relations strategy; and (3) the impact of school and community relations. This study used a qualitative approach with case study design. Data collection techniques through interviews, documentation studies, and observations. The data analysis process is carried out by collecting, condensing, presenting, and drawing conclusions/verification. The results of the research show that: (1) the role of school and community relations consisting of: relations, supporters, communicators, and publicists is carried out well, according to the results of the principal's management and support from the school community; (2) school and community relations strategies are carried out in various ways through internal and external programs, where internal programs include various activities within the school (meetings, completeness of infrastructure, developing teacher competency, placement of resources according to interests and talents, as well as publications via social media). External relations consist of several programs involving the general public and government agencies, either directly or indirectly; (3) the impact of school and community relations involving parties within the school or the wider community, this causes school members to become more confident and motivated, increased trust among internal parties, increasingly conducive relationships within the school, an increase in the image of the school's human resources, the number of relationships, complete facilities. And infrastructure. The impact outside the school that occurs, explains the branding and building of the school, increasing public interest, good competitiveness, creating satisfaction with parents, improving the school's image, and spreading positive information in the community.